Social frailty predicts worse outcomes in patients with multiple myeloma: A novelty in an old approach - Toshiki Terao; Takafumi Tsushima; Daisuke Miura; Kentaro Narita; Masami Takeuchi; Kosei Matsue (eJHaem, 2020)
Abstract Social frailty, defined as the loss of social roles and networks in the community, has never been evaluated in patients with multiple myeloma (MM). This study aimed to evaluate the usefulness of social frailty as a predictor of survival in MM. We retrospectively reviewed 237 consecutive patients with MM from 2009 to 2019. Activities of daily living (ADL), the instrumental ADL score, the Charlson Comorbidity Index, and factors to evaluate social relationships were routinely assessed at the time of initial diagnosis and first hospitalization at our center by hematological clinicians, nurses, and rehabilitation staff. Social frailty was evaluated using five social factors and was defined as a score of at least 2 points. Overall, 69 (30.0%) patients were defined as socially frail, with a median score of 0. Those who were socially frail showed significantly shorter progression‐free and overall survival than those who were not. Using the International Staging System, International Myeloma Working Group frailty score, and social frailty, we developed two staging systems, and these further demonstrated the importance of assessing frail patients with MM. Our findings have identified the usefulness for evaluating social frailty; however, to confirm our results, an independent study with larger patient numbers with an entirely prospective assessment is needed to confirm their results.